Religious Actors in Contemporary World Politics: Preconditions, Possibilities and Development Prospects - V. V. Tolkachev (Vestnik MGIMO-Universiteta)
As data transmission accelerates and more and more people get access to information, it is becoming increasingly important to take into account ethnic, cultural, religious and civilizational differences in order to avoid undesirable consequences, many of which can have a global effect. The events that took place in the last decades of the XXth century demonstrate the return of religion into mass consciousness - a development which can influence political behaviour of large groups of people.